Gaya Kepemimpinan Transaksional Dan Pembinaan Kepala Sekolah Untuk Membentuk Perilaku Kolaboratif Guru - Sabariah Sabariah; Aliah Aliah; Habibah Habibah; Citra Aulia Uzliva (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The aim of the research is to describe the transactional leadership style and coaching of school principals to shape the collaborative behavior of teachers at SDN 1 Sarigadung, Tanah Bumbu, South Kalimantan. Qualitative research method through case studies. Data collection techniques using interviews, observation and documentation. Data processing techniques using reduction, data presentation and drawing conclusions. Data validity techniques with triangulation of sources and techniques and confirmability. Research results: Teachers' collaborative behavior is demonstrated by their mastery of combining new and old material, forming student study groups, being a place for students to vent and demonstrate teaching material in front of the class. Transactional leadership to form collaborative behavior by providing motivation and giving rewards to teacher performance. The coaching provided includes class visits, personal meetings, teacher meetings, inter-school visits and work group meetings